Simulated real-time lunar volatiles prospecting with a rover-borne neutron spectrometer. Issue 10 (15th May 2015) - Elphic, Richard C.; Heldmann, Jennifer L.; Marinova, Margarita M.; Colaprete, Anthony; Fritzler, Erin L.; McMurray, Robert E.; Morse, Stephanie; Roush, Ted L.; Stoker, Carol R.; Deans, Matthew C.; Smith, Trey F.
Highlights In situ resource utilization may revolutionize human lunar exploration. Robotic missions to identify and characterize natural resources are needed. Field test of rover-borne neutron spectrometer has shown operational feasibility.